Kütüphane Fihristlerinin Tenkitli Neşrine Doğru: Fâzıl Ahmed Paşa Koleksiyonuna Ait Defterlerin Mukayesesi - AÇIL, BERAT (My University, 2023)
Türkiye akademisinde hatırı sayılır bir tenkitli neşir tecrübesi bulunmaktadır. Son zamanlarda tenkitli neşir uygulamalarına ilaveten tenkitli neşir nazariyesine yönelik çalışmalarda da bir artış meydana gelmiştir. Bu gelişmeler tenkitli neşir nazariyesinin daha ayrıntılı bir şekilde ele alınmasını ve bugüne kadar tenkitli neşre konu olmamış metinlerin de tenkitli neşir usullerine göre neşredilmesini gündeme getirmiştir. Bu bağlamda kütüphane, koleksiyon, kültür tarihi, bilim tarihi gibi alanların vazgeçilmez kaynaklarından biri olan kütüphane fihristleri/defterleri de tenkitli neşre konu olabilecek malzemelerden biri olarak öne çıkmaktadır. Birden fazla fihristi, defteri hatta kataloğu mevcut kütüphane veya koleksiyonların gelişimlerini izlemenin bir yolu da söz konusu defterleri mukayese ederek tenkitli neşirlerini hazırlamak, böylece söz konusu kütüphanenin nihai envanterini ortaya çıkarmaktır. Daha önce hakkında çokça çalışma yapılmış olan Fâzıl Ahmed Paşa Koleksiyonu birçok meziyetinin yanı sıra birden fazla deftere sahip olması açısından da dikkate değerdir. Bu tebliğ, söz konusu koleksiyonun gelişimini defterler üzerinden okumayı ve envanterdeki eksilme ve ilaveleri ortaya çıkararak koleksiyonun nihai kataloğunu belirlemeyi amaçlamaktadır. Sonuçta kütüphane defterlerinin de tenkitli neşre tâbi olması gerektiği ve bu tarz bir yaklaşımın kütüphane tarihi çalışmalarına yeni bir bakış açısı getireceği iddia edilmektedir.

There is considerable experience in preparing and publishing critical editions of the Arabic-alphabet texts in Turkey. Recently, in addition to this growing practice, there has been an increase in studies looking at different aspects of critical edition publication theory. These developments led to more detailed discussions on what critical edition is and created a suitable ground to publish texts that have not been published so far. It is within this context that library catalogs, or daftars (Turkish: defter), which are one of the indispensable resources for researchers in the fields of library, library collection, cultural history, and history of science, emerged as one of the materials that can be the subject of critical edition practices. There are many ways to understand the development of a library or a collection. Analyzing the catalogs of libraries and library collections comparatively is one of them. Making critically edited historical catalogs ready at hand is a fruitful effort that would help researchers to finalize any sorts of discussions on the full inventory of a library or a collection. The well-studied Fazıl Ahmed Pasha Collection in the Köprülü Manuscript Library is notable for its many features as well as for having more than one catalog. Based on these catalogs, this paper aims to show the historical development of the collection, to highlight what was extracted from and added to the inventory, and to create an ultimate and reliable catalog of the collection. The paper argues that the catalogs of the Ottoman libraries should be subject to increasing critical edition experience and practice in the country given the fact that they have the potential to bring new perspectives and approaches to the study of the history of libraries.
Towards a Critical Edition of the Ottoman Library Catalogs (Defters): A Comparison of the Catalogs of the Fazıl Ahmed Pasha Manuscript Collection